"Pretty Much Fear!!" Rationalizing Teacher (Dis)Engagement in Social Justice Education. Issue 2 (2nd April 2016) - Baily, Supriya; Katradis, Maria
ABSTRACT: This article analyzes how teachers in U.S. classrooms navigate, dialogue, debate, and absorb the ideas of privilege, power, and the presence of various forms of injustices. Through their understanding of these topics, we explore how K-12 teachers engage, disengage, and rationalize issues of social justice in education, society, and their own classrooms. This article utilizes teachers' dialogue through one curricular design used by a group of teacher educators to ensure safety, dialogue, and reflection. Using a grounded theory approach, we find that teachers lie on a continuum somewhere between shirking or embracing their role and responsibilities towards social justice. By highlighting K-12 teachers' understandings and positionalities regarding social justice, this study helps teacher educators charged with preparing teachers to better recognize the challenges we face in bringing social justice curricula to teacher education programs.